Experimental investigation of delamination damage for glass fiber-reinforced polymer composite during abrasive waterjet machining - Hashim, Hanizam; Mazli, Nur Hisyam Afandi; Ramli, Mohd Irman; Abdul Rasib, Amir Hamzah; Baba, Nor Bahiyah (School of Engineering, Taylor’s University, 2025)
Delamination damage of glass fibre-reinforced polymer (GFRP) composite in abrasive waterjet machining (AWJM) is still a major issue. The main AWJM parameters that have a significant impact on delamination vary depending on the type of GFRP especially for marine applications. Hence, a Taguchi method of L8 orthogonal array design of experiment carried out to optimize the traverse speed (TS), standoff distance (SOD) and waterjet pressure (WP) parameters of AWJM on 8-layer GFRP ship panel. The results revealed that SOD has the most significant impact on delamination damage and followed by WP and TS were ranked 2 and 3, respectively. The optimized combination was at parameters of SOD (5 mm), WP (150 MPa) and TS (38 mm/min), which gave a minimum delamination radius of 6.25 mm. The delamination trend decreases at the increase of SOD and TS but increases at the higher of WP. The delamination damage starts at the piercing instance and travels further into the fibre layers during cutting. Further investigations on controlling the piercing factors shall help to reduce this damage.